Dynamics of water evaporation from porous asphalt. (30th March 2019) - Aboufoul, M.; Shokri, N.; Saleh, E.; Tuck, C.; Garcia, A.
Highlights: Water evaporation from porous asphalt is related to the pore space topology. Stage-1 evaporation is defined by liquid evaporation at the asphalt's surface. Stage-2 evaporation depends on the porosity and tortuosity of the asphalt. An analytical model was developed to estimate the evaporation rates from asphalt. Abstract: The dynamics of water evaporation from porous asphalt mixture, with porosity ranging from 15% to 29%, have been investigated in this article. In order to test the same samples under different conditions, the pore structure of asphalt was quantified using X-ray Computed Tomography (CT) scans and 3D printed in transparent resin blocks. 3D printed transparent resin samples were tested under controlled laboratory conditions to understand the effect of pore space topology on the water retention and drying dynamics. The macroporosity, pore size distribution, air void tortuosity, water conductivity, and water retention curves of the 3D printed porous asphalt samples were quantified by means of image analysis. Moreover, a model was developed and tested experimentally to estimate the evaporation rates from porous asphalt materials under a wide range of porosities. Within the range of asphalt mixtures studied in the present work, the evaporation rate is related predominantly to the porosity, pore size distribution and tortuosity. It was found that the period over which water evaporation occurs at the surface is relatively short during drying of porous asphalt materials due to their relatively large pores weakening the capillary forces. This results in significantly shortening the so-called stage-1 evaporation (when the drying rate is controlled by liquid vaporisation at the surface) and early onset of the transition period (when both surface water evaporation and vapour diffusion inside porous asphalt play a comparable role in supplying the evaporative demand). The transition period is followed by the stage-2 evaporation when the process is limited by the vapour diffusion inside the porous asphalt. Our results illustrate that the beginning of the stage-2 evaporation depends on the porosity and tortuosity of the porous asphalt material among other parameters. Our results and analysis provide new insights into the dynamics of water evaporation from asphalt materials.